Estudos filogenéticos moleculares em Metastelmatinae (Asclepiadoideae, Apocynaceae) - Silva, Uiara Catharina Soares e (2010)
[Molecular phylogenetic studies in Metastelmatinae (Asclepiadoideae, Apocynaceae)] Metastelmatinae is widely distributed in the Neotropic and most diversified in mountain ranges of the northwestern South America and Central Brasil, besides Caribbean islands. It includes 13 genera and about 260 species with complex relationships, possibly caused by the rapid and recent diversification of the lineage at 12 million years ago. The aim of this study is to recover the phylogeny of Metastelmatinae using molecular data and more than 70 species of the subtribe. During the expeditions, rare species were collected to fill important taxonomic gaps, including Hemipogon abietoides, known only because of the type collected in 1825 and whose taxonomic affinities have been discussed. For phylogenetic analyses, the plastidial regions trnT-F, trnS-G, rps16, matK, psbA, and trnE-Y, these last two are used for the first time in the family, and the nuclear ITS were sequenced. Parsimony analyses and Bayesian inferences produced several conflicts between plastidial regions and ITS. Topological information from the trees generated with plastidial regions and with ITS were fused in a Supertree. Nine clades emerged from the plastidial combined analyses, but only two of them were recovered by ITS. The Supertree presented 18 supported clades, 23 equivocal clades and 15 clades that conflict with the source trees. There is not any genus that emerged as monophyletic, but some patterns could be detected. Affinities between erect and voluble species of Hemipogon from the Espinhaço Range previously included in Astephanus and Metastelma presented high support. Macroditassa is polyphyletic, having M. melhantha among species of Ditassa whereas M. adnata (the type of the genus) and M. macrophylla form a grade to Peplonia, which justify the synonymization of the former genus in the latter. Likewise, without Barjonia harleyi and Hemipgon harleyi, Minaria is paraphyletic, justifying the transference of the two species to Minaria.